PENGAMBILAN KEPUTUSAN DALAM MEMILIH FOTOGRAFER WEDDING - Buana, Tommy Pradhipta; Sulandari, Santi (Jurnal Ilmiah Penelitian Psikologi, 2021)
Marriage is a sacred moment, where men and women unite in bonds according to laws, norms, and religions. A lot of people nowadays has a big desire to capture this moment into a memorable photo. Many wedding photo service providers undoubtedly make consumers feel confused about their choice of photo vendors. This research has fundamental question about "decision making in choosing a wedding photographer?” As well as aiming to see the factors that influence decision making in chooing a wedding photographer. This study used a quantitative desrtiptive method that was conducted on 73 people who lives in Solo and married in 2019-2020. Results of this study indicate that respondents are more concerned with quality while price is second. Quality is a major factor for someone contacting a wedding photo service providers, but the main question that wedding photo services providers will ask by the customers is about price. However, the main thing that made respondents choose to use certain wedding photo services was the quality or result of the photos